Implementasi Web Service DenganMetode Rest Pada Layanan Sales Order di UD Lancar Semarang - Andreas Sutanto, Felix; Nur Iksani, Muchamad (Information Technology and Telematics, 2019)
ABSTRACT UD Lancar is one of the companies engaged in the sale of making invitation orders in Semarang. But now the process of buying and selling is still done with the way the buyer must order through a smooth UD outlet available in Semarang. Information that supports the smooth running of UD's business by distributing brochures and social media. Therefore UD smoothly wants to facilitate access to buying and selling and ordering online. By making an online application the buyer can choose directly and order without having to go to the UD outlet smoothly. The method used is REST, a method that uses a client server and uses PHP MySQL